What is Urgency of Health-Seeking Behaviour Concept in Health Policy? - Rachmat Hidayat; Patricia Wulandari (Open Access Indonesia Journal of Social Sciences, 2020)
Abstract Health-seeking behavior (HSB) is a concept that requires contributions from multidisciplinary sciences, namely health, psychology, and social sciences. Understanding the HSB concept helps academics and practitioners to understand the individual's reasons for seeking medical help. Health service facility factors are generally often blamed for the low quality of health in a place; for example, the low quality of health in the village is often associated with the limitations of health facilities in the village compared to in the city. It turns out that not all of them and not the majority of the low quality of health in an area is only due to the limitations of health facilities, sometimes it can be caused by the values held by the local community.